Financial development and human capital thresholds for the infrastructure development-industrialization nexus in Africa - Guivis Zeufack Nkemgha; Tii Njivukuh Nchofoung; Fabien Sundjo (African Governance and Development Institute (AGDI), 2022)
Examining the value-added link between infrastructure and industrialization is fundamental to achieving Sustainable Development Goal (SDG) 9, which consists of building resilient infrastructure, promoting inclusive and sustainable industrialization and fostering innovation. The objectives of this paper are to analyse the effect of infrastructures on industrialisation and how financial development and human capital modulate this effect in 33 African countries during the period 2003-2019 through the system GMM methodology. The results show that infrastructural development has a direct enhancing effect on industrialisation in Africa. When the indirect effect regressions through the modulating effects of financial development and human capital are considered, the net effects are equally positive though the results vary across the different specifications of infrastructure and the specific transmission channel considered. For instance, the indirect effect through the interaction of electricity and transport infrastructures with financial development and human capital produced a negative net effect. The thresholds of financial development and human capital required to nullify these negative effects are provided and practical policy implications are discussed.
Keywords: H54; L60; O55; 330; infrastructures; industrialization; financial development; human capital